Leadership structure: Separating the CEO and Chairman of the Board - Brickley, James A.; Coles, Jeffrey L.; Jarrell, Gregg (Journal of Corporate Finance, 1997)
Shareholder activists and regulators are pressuring U.S. firms to separate the titles of CEO and Chairman of the Board. They argue that separating the titles will reduce agency costs in corporations and improve performance. The existing empirical evidence appears to support this view. We argue that this separation has potential costs, as well as potential benefits. In contrast to most of the previous empirical work, our evidence suggests that the costs of separation are larger than the benefits for most large firms.